Prevalence, presentation and prognosis of delirium in older people in the population, at home and in long term care: a review. (18th April 2012) - de, E.; Verhaak, P. F. M.; van der, K.
<x xml:space="preserve">Abstract</x> Objective The aim of this study is to provide an overview of prevalence, symptoms, risk factors and prognosis of delirium in primary care and institutionalized long‐term care. Design The method used in this study is a systematic PubMed search and literature review. Results The prevalence of delirium in the population among the elderly aged 65+ years is 1–2%. Prevalence rises with age: 10% among a "general" population aged 85+ years. Prevalence rises up to 22% in populations with higher percentages of demented elder. In long‐term care, prevalence ranges between 1.4% and 70%, depending on diagnostic criteria and on the prevalence of dementia. There is a significant increase of the risk of delirium with age and cognitive decline in all groups. Concerning prognosis, most studies agree that older people who previously experienced delirium have a higher risk of dementia and a higher mortality rate. Population and long‐term care studies show the same tendency. Conclusions Delirium in a non‐selected population aged 65+ years is uncommon. However, prevalence rises very quickly in selected older groups. Primary care doctors should be aware of a relatively high risk of delirium among the elderly in long‐term care, those older than 85 years and those with dementia. Copyright © 2012 John Wiley & Sons, Ltd.